Organizacja i finansowanie gospodarki komunalnej w Polsce - Kaleta, Józef (Wydział Prawa i Administracji UAM, 1966)
The existing scope of municipal economy in Poland is somewhat too large. The hotels, zoological gardens, botanical gardens etc., which do not render services of a strictly municipal character (the essence of said services consists of meeting the everyday requirements of the local population), should not be included in this field of economy. The activity of some of the municipal establishments, especially of those which render services free of charge (e. g. the town sanitary services) can not be based on the principle of economic calculation. The best organisational form would be in that case the form of budgetary establishments. Enterprises and municipal establishments ought to be subordinated to the competent regional national councils (for boroughs or towns). It does not seem advisable to set up on a voivodship level a special corporation of enterprises and municipal establishments — parallel to the already existing departments of municipal economy at the voivodship national councils. The municipal enterprises and establishments are, as a rule, of a deficit character; the levied municipal fees and tariffs do not fully cover the operation costs and the deficit is being balanced by subsidies coming from the budgets of the regional national councils. That is — in fact — a characteristic feature of the municipal enterprises, which distinguishes them from any other regional enterprises. The municipal fees and tariffs which do not fully cover the costs of services rendered are causing many negative economic and social results. The raising of municipal fees and tariffs ought to be accompanied by simultaneous recompensation provided for the family budgets. A specific institution of the municipal financing system is the institution of shares of some business enterprises in the municipal investments costs. In practice, however, there are great difficulties first of all in fixing the portions of the shares and secondly in collecting them.